Effect of Impulse Buying on Socioeconomic Factors and Retail Categories - Rupesh Kumar, M.; Narayanan, A. G. V. (Indian Journal of Marketing, 2016)
The study aimed to determine the impulse buying behaviour of shoppers at apparel multi-brand outlets using socio-economic factors and retail categories. The research is a descriptive one, and it was conducted among 400 Indian respondents. This research was carried out to identify the impulsive behaviour of respondents at multi-brand outlets because it occurs high in organized retail stores due to attractive displays and latest design and collections. The study revealed that impulse buying behaviour varies among the distinct age profile. The study found that men shop more impulsively than women. The impulse buying did not have a high impact on changes in monthly family income of the respondents. The impulse buying behaviour was displayed more within the same multi-brand outlets than the other retail categories.